2012
DOI: 10.1136/bjophthalmol-2011-301378
|View full text |Cite
|
Sign up to set email alerts
|

The number of ophthalmologists in practice and training worldwide: a growing gap despite more than 200 000 practitioners

Abstract: The survey results show that despite over 200,000 ophthalmologists worldwide, there is currently a significant shortfall of ophthalmologists in developing countries. Furthermore, although the number of practitioners is increasing in developed countries, the population aged 60+ is growing at twice the rate of the profession. To meet this widening gap between need and supply, it is necessary to aggressively train eye care teams now to alleviate the current and anticipated deficit of ophthalmologists worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
224
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(229 citation statements)
references
References 1 publication
0
224
0
5
Order By: Relevance
“…Figures from 2010 showed that the United Kingdom has the lowest ratio of ophthalmologists per head of the population in the European Union (5.2 per 100 000). 6 The challenges of providing increased capacity coupled with reduced numbers of medically trained staff have been acknowledged by the Royal College of Ophthalmologists. 7,8 The Royal College of Ophthalmologists position is that, where circumstances and facilities allow, intravitreal injections should be administered by a specialist doctor trained in the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Figures from 2010 showed that the United Kingdom has the lowest ratio of ophthalmologists per head of the population in the European Union (5.2 per 100 000). 6 The challenges of providing increased capacity coupled with reduced numbers of medically trained staff have been acknowledged by the Royal College of Ophthalmologists. 7,8 The Royal College of Ophthalmologists position is that, where circumstances and facilities allow, intravitreal injections should be administered by a specialist doctor trained in the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Of the mere total of 103 ophthalmologists for a population of 8.075 million in Honduras, a large majority serve within urban cities, and it is not known how many actively perform eye surgeries. 6,7 Additionally, owing to rural healthcare barriers, many rural dwellers have severe and uncontrolled hypertension and diabetes; consequently, outreach programs, including one run by ZOE Eye Clinic in Tegucigalpa, Honduras, often deny these patients candidacy for subsidized cataract surgeries due to increased surgical and post-operational concerns. [7][8][9] Thus, uncontrolled diabetes and cardiovascular risks, such as hypertension, compound harm for eye health; not only do they increase the likelihood of cataract development, they also hinder patients from receiving surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[12] For instance, in 2012, the number of ophthalmologists per million population is 112 in France, 81 in Germany, and 99 in Switzerland. [13] Despite its apparent advantage due to its speed and ease of application, this approach often does not consider factors such as productivity, utilization, and distribution of healthcare personnel, making interpretation of the results difficult. Therefore, the problem of unequal distribution of healthcare workforce is likely to persist even with the projected estimates.…”
Section: Health Workforce Forecasting Approachesmentioning
confidence: 99%